PERTUMBUHAN IKAN KERAPU (SERRANIDAE) PADA KERAMBA JARING APUNG DI PERAIRAN PESISIR TELUK KODEK DESA MALAKA LOMBOK BARAT - Langkosono, Langkosono (JURNAL BIOLOGI INDONESIA, 2006)
ABSTRACTGrowth of the Groupers (Serranidae) in Floating Net Cages at The Coastal WatersKodek Bay Malaka Village West Lombok. Study of rearing of Bararnundi cod(Cromilileptes altivelis), flowered cod (Ephinephelus fuscogutatus) and estuarygrouper (E. tauvia) at floating net cages was canied out on June to December 2004at the coastal water Kodek Bay MalakaViiage, West Lombok. There was sigdicantdifference in weight growth rate of groupers during observation (X count = 67.420and X2a 0.05 = 2 1.026 or X count > X2a 0.05) during observation, but not in length (X2count = 0.998 and X2a 0.05 = 2 1.026 or X count < X2a 0.05). Observed physicochemicalproperties of experimental set up are water temperature between 27.2 - 27.8 OC, salinitybetween 3 1.8 - 33.8 %o, transparency between 10.3 - 14.5 m, air temperature between26.6 - 27.28 OC and pH about 8.3 - 8.4.Key word: Groupers fish of growth, waters condition